Morphology description of early larval stages of the Asian horseshoe crab, Tachypleus gigas and their exuviae - Kassim, Zaleha; Md Razak, Mohd Razali; Ramli, Riwan; Ahmad, Zuhairi; Ramli, Rohayu (IFERP Explore, 2023)
Young horseshoe crabs undergo ecdysis to grow and leave behind their old exoskeleton, or exuviae, but our knowledge of the morphology of both the exoskeleton and exuviae are scarce. This study aimed to investigate the process through a Scanning Electron Microscope (SEM) approach. The exuviae from the first and second ecdysis of the instars of Tachypleus gigas were collected right away after each molting, carefully dried, and critical-point dried before coated with gold. The same preparation was made to examine the morphological feature for instars. They were then examined with the SEM. All prosomal appendages are in a complete form during the first instar stage. The second instar stage is noted with the presence of the telson. The exuviae from instars 1, and 2 showed consistently the suture opening located along the anterior edge of the prosoma. This suture is absent from the exoskeleton of the larvae. There are notably two hinge pores located at both ends of the hinge which is the central dorsal part that joins the prosoma and opisthosoma which are absent on the intact larvae’s exoskeleton. The findings contribute to further improving the understanding of early growth and ecdysis in this living fossil.